Oncologists’ Recommendations of Clinical Trial Participation to Patients - Eggly, Susan (2007)
OBJECTIVE: To describe the frequency, context and type of oncologists’ recommendations to patients that they participate in a clinical trial and to analyze the relationship between recommendations and patients’ decisions to participate. METHODS: Data included 38 video recorded outpatient interactions during which 15 oncologists invited 38 patients to participate in clinical trials. We described the frequency, context, and type of oncologists’ recommendations and analyzed the relationship between these factors and patient decisions to participate and socio-demographic characteristics. RESULTS: Sixty-eight percent (n = 26) of the 38 interactions included an explicit recommendation. Most recommendations were unprompted by patients and/or companions and were tailored to individual patients. A significant relationship was found between recommendations and patients’ decisions to participate. Positive trends were found between receiving a recommendation and being female and having higher education. CONCLUSION: Oncologists routinely make recommendations to patients during the presentation of clinical trials. These recommendations may influence patients’ decisions and may occur more frequently with some demographic groups. PRACTICE IMPLICATIONS: Oncologists should be aware of the potential influence of their recommendations when discussing clinical trials with patients.